2004
DOI: 10.1002/rcm.1710
|View full text |Cite
|
Sign up to set email alerts
|

UV laser ablation of GdCa4O(BO3)3 (GdCOB) investigated by Fourier transform ion cyclotron resonance mass spectrometry

Abstract: The ions generated by laser ablation (LA) of calcium and gadolinium oxoborate GdCa4O(BO3)3 (GdCOB) were investigated by Fourier transform ion cyclotron resonance mass spectrometry (FTICRMS), a powerful tool for the characterization of ionic species produced by laser interaction with solid material. In order to better understand the matter transfer and the mechanism of thin film growth by pulsed-laser deposition (PLD), cationic and anionic clusters generated by UV laser ablation of GdCOB bulk material were stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Alternatively, mass spectrometry coupled to laser ablation (LA-MS) provides information on atomic and cluster species present in the gas phase. When considering the ionic fraction of species ejected in vacuum under laser irradiation, relevant information may be obtained on the atomic and high mass cluster species present in the gas phase above the target after laser-matter interactions [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, mass spectrometry coupled to laser ablation (LA-MS) provides information on atomic and cluster species present in the gas phase. When considering the ionic fraction of species ejected in vacuum under laser irradiation, relevant information may be obtained on the atomic and high mass cluster species present in the gas phase above the target after laser-matter interactions [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Sputter desorption can employ either projectiles (neutral or charged atoms or molecules) or laser pulses. In the projectile category, Gianotto and Groenewold investigated a variety of aluminum, silicon, and chromium oxides, generating small-to-medium sized cluster ions with rhenium tetroxide (ReO 4 − ) as the projectile. Laser ablation is more commonly used, and Aubriet and Gaumet have used it for forming alumina, silica, and d-block oxyanions. Laser irradiation has also enjoyed extensive use for forming metal oxide clusters by targeting the laser on a rotating metal rod as pioneered by several groups, enabling study of a wide variety of transition metal oxides; this approach tends to form hypo-oxidized species, and the extent of oxidation can be manipulated by seeding the ablation region with oxygen.…”
Section: Introductionmentioning
confidence: 99%
“…It has mainly been suggested that large clusters and droplets are the major constituents of the ablated mass fraction 16. The role of laser parameters like wavelength, laser pulse duration, laser fluence, etc., is important and it has been discussed in several papers 17–20. In this work we have studied clusters formed during laser ablation using a 337 nm laser that is part of a commercial instrument.…”
mentioning
confidence: 99%